Analisis Strategi Komunikasi Personal Branding Bupati Kabupaten Luwu Timur dalam Meningkatkan Kepercayaan Masyarakat - Heldayanti Heldayanti; Tuti Bahfiarti; Yusmanizar Yusmanizar (MUKASI: Jurnal Ilmu Komunikasi, 2024)
This study aims to analyze and clearly describe the Personal Branding communication strategy used by the Regent of East Luwu Regency, Budiman in increasing public trust during his leadership period from April 5, 2021 to April 5, 2024. This research was conducted in East Luwu Regency. Data collection was carried out through observation, interviews, documentation and literature review. This research uses a descriptive qualitative approach. In building Personal Branding , a person needs an effective and targeted communication strategy so that the ultimate goal of Personal Branding is in accordance with the desired results. From the research of this study it was found that: The Personal Branding Communication Strategy of the Regent of East Luwu Regency using “Luwu Timur Inspiring” with the main target of the realization of the Regional Government's priority program has increased public trust supported by the results of the East Luwu BPS Survey reaching 87.84 percent with a good category of people Satisfied with Public Services under the leadership of Budiman. Budiman's SWOT includes, Strength: the realization of regional priority programs including One Room One Patient, Green Open Space Development without APBD, Special Financial Assistance (BKK) for 125 Villages, Weakness: Limited authority over regional development. Opportunity: the characteristics of a friendly personality who smiles and cares, and easily mingles in the local community, Threats: Policy changes from the center. Obstacles to the Personal Branding Communication Strategy of the Regent of East Luwu Regency, namely: Time and team limitations and lack of interaction with social media users.